Effect of Radiation Damage on SM-1, SM-1A and PM-2A Reactor Vessels - McLaughlin, D. W.; Rowekamp, B. J.; Chittum, R. A.; Coombe, J. R.; Kelleman, R. W.; Bobe, P. E.; Clancy, E. F. (U.S. Atomic Energy Commission. Division of Technical Information., 1961)
Report describing the status of the SM-1, SM-1A, and PM-2A reactors, specifically regarding the effects "of irradiation on nil-ductility transition temperature and the associated problem of brittle fracture." (p. iii)